The ANALYSIS OF A PHASE-SHIFT-CONTROLLED ACTIVE BOOST RECTIFIER FOR SOFT-SWITCHING DC-DC CONVERTERS (International Journal of Engineering Management Science, 2022)
High efficiency and high power density can be achieved with a dc–dc transformer by operating all the switches at a fixed 50% duty cycle. However, the output voltage of the dc–dc transformer cannot be regulated. Novel rectifiers named active boost rectifiers (ABRs) are proposed in this paper. Basically, an ABR iis composed of a traditional diode rectifier and a bidirectional switch. By adopting phase-shift control between the primary- andsecondary-side switches, the output voltage regulation can be achieved when introducing the ABR to a dc–dc transformer. As a result, a family of novel soft-switching dc–dc converters is harvested. When the proposed converter operates in the soft-switching continuous conduction mode, zero-voltage switching (ZVS) performance for all the primary- and secondary side switches is achieved. When the converter operates in the discontinuous conduction mode, zero current switching (ZCS) for the primary-side switches and ZVS for the secondary-side switches are achieved. By receiving stage shift control between the essential and optional side switches, the yield voltage direction can be accomplished while acquainting the ABR with a dc–dc transformer.  Subsequently, a group of novel delicate exchanging dc–dc converters is gathered. At the point when the proposed converter works in the delicate exchanging ceaseless conduction mode, zero voltage exchanging (ZVS) execution for all the essential and optional side switches is accomplished. At the point when the converter works in the inconsistent conduction mode, zero current exchanging (ZCS) for the essential side switches and ZVS for the optional side switches are accomplished